Rural Extreme Poverty: Governance and Alleviation Efforts - Herdiana, Dian (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Extreme poverty in villages is caused by many factors and is complex, so it requires comprehensive mitigation. This article intends to explain the complexity of extreme poverty in villages and provide solutions to overcome it. This research uses descriptive research methods with a qualitative approach. The research results show that the background of poor community groups in villages is based on age, level of education, physical condition, capital ownership, livelihood, and number of dependents in the family. Meanwhile, factors that cause extreme poverty in villages include capital ownership, quality of human resources, culture and social networks, opportunity and opportunity, and access to power. Solutions for overcoming extreme poverty in villages should be carried out based on comprehensive, multi-aspected, and sustainable community empowerment efforts so that they will not only create economic productivity but also community resilience and independence to obtain a prosperous and quality life.